Verbal working memory and short-term memory : bilingual vs monolingual children - Ozfidan, Burhan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Language learning is an incredible process for children. The study aims to assess the effect of early L2 immersion on L1 development and phonological working memory, and short-term memory. Specifically, the researcher compared the performance of a group of bilinguals and monolinguals aged 5-7. This study from a cognitive perspective supports the hypothesis that exposure to an L2 in sequential bilingual children exerts an affirmative influence on their cognitive development. There were 56 Turkish-speaking upper-middle-class students as participants of the study. The researcher designed to examine the impact of L2 learning on phonological shortterm and working memory development by performing tasks measuring phonological working memory and shortterm memory and L1 linguistic skills in a group of bilinguals and monolinguals. The findings reflected that bilingual students outperformed their monolingual peers once the bilinguals’ performance with monolinguals was compared to all possible variables. The study results support the hypothesis that intensive and early exposure to an L2 may increase verbal working memory and verbal short-term memory abilities in sequential bilingual children while not decreasing their linguistic performance in L1. The results of articulatory abilities, naming, phonological discrimination, sentence completion, and grammatical comprehension assessments indicated that bilinguals notably performed better than monolinguals. This indicates that exposure to L1 enables bilingual children to develop the L1 for a significant amount of time sufficiently.